2022
DOI: 10.3389/feduc.2021.817711
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Versus Remote: Effects of an Intervention in Reading Fluency During COVID-19 Pandemic

Abstract: Fluency is a central skill for successful reading. Research has provided evidence that systematic reading fluency interventions can be effective. However, research is scarce on the effects of interventions delivered remotely versus face-to-face. This study investigated the efficacy of a systematic and standardized intervention for promoting reading fluency in third-grade students (N = 207) during the COVID-19 pandemic. The study had a pretest, posttest, and follow-up design, with two intervention groups (remot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Additionally, it is worth noting that the students participating in this study were in an early stage of reading acquisition, and all of them were experiencing difficulties in the automatization of reading. In the first years of schooling, phonics and fluency instruction are key components in literacy instruction in the classroom (Spear-Swerling et al, 2016) and research has suggested that struggling readers obtain the largest gains with systematic reading interventions (Suggate, 2010;Cruz et al, 2021). Therefore, the characteristics of our sample might have played a role in the large gains observed in word reading and oral reading fluency.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, it is worth noting that the students participating in this study were in an early stage of reading acquisition, and all of them were experiencing difficulties in the automatization of reading. In the first years of schooling, phonics and fluency instruction are key components in literacy instruction in the classroom (Spear-Swerling et al, 2016) and research has suggested that struggling readers obtain the largest gains with systematic reading interventions (Suggate, 2010;Cruz et al, 2021). Therefore, the characteristics of our sample might have played a role in the large gains observed in word reading and oral reading fluency.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, there were some attempts to create interventions that could be delivered remotely to children with learning disabilities. However, most of these consisted of delivering traditional interventions using programs such as Zoom for synchronous remote communication (e.g., Alves and Romig, 2021;Beach et al, 2021;Cruz et al, 2021). In this study, the intervention started face-to-face in November of 2020 but was shifted to a remote modality between January and March of 2021 due to lockdown.…”
Section: The Present Studymentioning
confidence: 99%
“…In the second moment of data collection (February – March 2021), parents were asked to answer to the same items based on their current experiences during the second lockdown. The study was approved by the ethics committee of Lusíada University, following the guidelines of the Psychology for Positive Development Research Center (CIPD/2122/DEED/1), and was part of a larger research project focused on reading skills of third graders (Cruz et al, 2022 ). The study was presented to parents by their children's teachers.…”
Section: Methodsmentioning
confidence: 99%
“…It assumes the adoption of strategies through explicit, consistent, and systematized teaching practices, demanding the use of specific methodologies and allowing adequate time for learning and training. The first years of school are deemed pivotal in the process of learning to read, and they are frequently marked by families and teacher's high expectations regarding children's success (Stern, 2006;Cruz et al, 2022). It is also during the first years of formal education that learning difficulties associated with reading emerge, highlighting the relevance of early assessment and intervention so that students have a better chance of overcoming them.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of written material, reading a text is thought to be a more accurate predictor of fluency (Wanzek et al, 2016). There have been few studies that analyze reading fluency in European Portuguese primary school children (Fernandes et al, 2017;Cruz et al, 2022). Key findings highlight the influence of word recognition skills in the development of reading fluency, as well as the intrinsic relationship between the latter and vocabulary acquisition, particularly in the early grades (Fernandes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%